The main Removal Mechanism of Organic micropollutants and Organisms in an Irrigation System using Untreated Wastewater - Chávez-Mejía, Alma C.; Magaña-López, Rafael; Durán-Álvarez, Juan Carlos; Jiménez-Cisneros, Blanca Elena (International Journal of Environment, Agriculture and Biotechnology, 2019)
The presence of organic micropollutants on residual water used for irrigation is common in development countries, and their human impacts and the ecological consequences are still completely unknown. The aim of this study was to determine the main mechanisms involved during removal of three organic compounds (carbamazepine, ibuporfen, and 4-nonylphenol), and three usually pathogenic organisms (Escherichia coli, Giardia lamblia and Ascaris lumbricoides) contained in untreated wastewater dumped to agricultural soil, based on laboratory studies with inoculated soil, as well as the corroboration with field measurements. The results suggest adsorption and biodegradation as the predominant processes responsible for the removal of all contaminants analyzed, reporting efficiencies greater than 95% during the first 30 cm of the soil depth. Nevertheless, the efficiency depends on the type of pollutant, and also the physicochemical characteristics of the soil. For ibuprofen and 4-nonylphenol occurs mostly by biodegradation, and the adsorption of carbamazepine is associated with the organic matter content, while E. coli is adsorbed to the clay fraction of the soil. Finally, G. lambia and A. lumbricoides removal is due to different processes from adsorption such as colloidal filtration.